PEMBERDAYAN MASYARAKAT UMKM BERBASIS DIGITAL LITERACY DI KAMPUNG LOGAM NGINGAS KABUPATEN SIDOARJO [EMPOWERMENT OF SME COMMUNITY BASED ON DIGITAL LITERACY IN KAMPUNG METAL NGINGAS, SIDOARJO REGENCY] - Allen Pranata Putra; Erwan Aristyanto (Universitas Pelita Harapan, 2021)
The quality of human resources will determine the sustainability of the economy in every condition, especially in the conditions of the Covid-19 pandemic, it takes the comparative sustainability of good products. In addition to comparative advantage, increasing digital literacy of each individual is also needed to be able to provide employment and economic improvement. Problems in UMKM are at least the improvement of human resources, the quality of product branding, the improvement of the economy periodically and the growth of employment. The methods used in improving digital literacy in community service are Focus Group Discussion (FGD), indepth interview, and field mentoring. Community empowerment activities are expected to increase the competence of UMKM actors due to technological transformation in business. The results of community empowerment through the improvement of digital literacy that has been done show positive results and are very beneficial for UMKM. At least UMKM can win competition in the lowest price filters, improved product branding, and increased labor. Further community service is expected to maintain the quality of products and comparative advantages that have been owned by UMKM actors.BAHASA INDONESIAN ABSTRACT: Kualitas sumber daya manusia akan menentukan keberlangsungan ekonomi dalam setiap kondisi, terutama dalam kondisi pandemi Covid-19, dibutuhkan keunggulan komparatif produk yang baik. Selain keunggulan komparatif, peningkatan digital literacy setiap individu juga diperlukan untuk dapat meningkatkan lapangan kerja dan peningkatan ekonomi. Masalah di UMKM setidaknya adalah peningkatan sumber daya manusia, kualitas branding product, peningkatan ekonomi secara berkala dan pertumbuhan lapangan kerja. Metode yang digunakan dalam meningkatkan digital literacy dalam pelayanan masyarakat adalah Focus Group Discussion (FGD), indepth interview, dan pendampingan lapangan. Kegiatan pemberdayaan masyarakat diharapkan dapat meningkatkan kompetensi pelaku UMKM akibat adanya tranformasi teknologi dalam bisnis. Hasil pemberdayaan masyarakat melalui peningkatan digital literacy yang telah dilakukan menunjukkan hasil yang positif dan sangat bermanfaat bagi pelaku UMKM. Setidaknya pelaku UMKM dapat memenangkan persaingan dalam filter harga terendah, peningkatan branding product, dan peningkatan tenaga kerja. Pengabdian masyarakat selanjutnya diharapkan dapat mempertahankan kualitas produk dan keunggulan komparatif yang telah dimiliki oleh pelaku UMKM.